Objectives and Motives of Western Journeys to the Arabian Peninsula - Nawab, Awatif Mohammed; Muhammad, Ibrahim Jalal Ahmad; Abu Qaid, Ahlam Ali Ahmad (Journal of Humanities & Social Sciences, 2022)
The Arabian Peninsula is considered an area of attraction and interest for many, as it occupies a distinguished geographical and strategic position as it is located in the heart of the world at the intersection point of the main transportation lines, and it links the Arabian Gulf with the Red Sea in the west, and links Levant and Iraq to the south of the Arabian Peninsula, which is the home of civilizations and the cradle of messages. I witnessed the arrival of a number of European travelers since the fifteenth century AD, and the goals and motives of these Western travelers who found all the support and encouragement from their countries varied and varied. In identifying many aspects of the history of the Arabian Peninsula, and its various geographical, political, economic and social aspects.The trips are an important source of the history of the Arabian Peninsula because of the important and valuable information they contain, and despite the information that was covered in the travel books and that the travelers gleaned from their trips, it is not possible to accept all the information contained therein without examination and consideration and without subjecting it to discussion and controversy.This research and its title: (Objectives and Motives of Western Journeys to the Arabian Peninsula) show some of those goals and motives, and the research included:Introduction: It includes the importance of the topic, the reason for choosing it, and the research method and plan.- First: The importance and objectives of western trips.Second: Motives for the western voyages to the western peninsula.Third: The reasons that prompted the travelers to take trips to the Arabian Peninsula.- Conclusion: The study concluded with the most important results the researcher, then it was followed by the proven sources, references and indexes.
Keywords: Journeys; the West; the Arabian Peninsula; history